2022
DOI: 10.1097/md.0000000000030907
|View full text |Cite
|
Sign up to set email alerts
|

Medication use during pregnancy and birth defects in Hunan province, China, during 2016–2019: A cross-sectional study

Abstract: Safety of drug use during pregnancy attracts attentions from clinicians, pregnant woman, and even the total society. However, the studies about medication use during pregnancy and the followed birth defects (BDs) are rare in Chinese. To study condition about medication use during pregnancy and the followed BDs in Hunan province of China, here a cross-sectional study was carried out. All women using medication during pregnancy and delivering fetuses with BDs in Hunan province, China, during 2016 to 2019 were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In tandem with this, our review also revealed that the intake of both prescribed and unprescribed drugs including herbal medication during the early onset of pregnancy was associated with NTDs. This finding was also supported in studies conducted elsewhere 34 35 131. In line with this, in Ethiopia, a significant number of pregnant mothers use herbal medication to alleviate symptoms, during the first trimester of pregnancy, shorten the duration of labour and reduce labour pain 132–134.…”
Section: Discussionmentioning
confidence: 54%
“…In tandem with this, our review also revealed that the intake of both prescribed and unprescribed drugs including herbal medication during the early onset of pregnancy was associated with NTDs. This finding was also supported in studies conducted elsewhere 34 35 131. In line with this, in Ethiopia, a significant number of pregnant mothers use herbal medication to alleviate symptoms, during the first trimester of pregnancy, shorten the duration of labour and reduce labour pain 132–134.…”
Section: Discussionmentioning
confidence: 54%